Effects of Nasal Continuous Positive Airway Pressure on Cerebral Hemodynamics in Preterm Infants - Han Zhou; Han Zhou; Xuewen Hou; Rui Cheng; Youyan Zhao; Jie Qiu (Frontiers Media S.A., 2020)
Background: To evaluate the effects of pressure levels on cerebral hemodynamics in premature infants receiving nasal continuous positive airway pressure (nCPAP) during the first 3 days of life.Methods: Forty-four preterm infants treated with nCPAP were divided into two groups: very preterm infants [gestational age 1 (GA1), GA < 32 weeks, n = 24] and moderate/late preterm infants (GA2 group, GA 32-37 weeks, n = 20). During monitoring, pressure levels were set at 4 → 6 → 8 → 4 cmH2O, and cerebral hemodynamics was assessed by near-infrared spectroscopy (NIRS). Vital signs, peripheral oxygen saturation (SpO2) and transcutaneous carbon dioxide pressure (TcPCO2) were simultaneously recorded.Results: Pressures of 4-8 cmH2O had no significant influence on cerebral hemodynamics, TcPCO2, SpO2 or other vital signs. The tissue oxygenation index (TOI), the difference between oxygenated hemoglobin (ΔHbO2) and deoxygenated hemoglobin (ΔHHb) (ΔHbD), and cerebral blood volume (ΔCBV) were all significantly positively correlated with gestational and post-natal age, with fluctuations being greater in the GA1 group. ΔHbD and ΔCBV were also significantly positively correlated with TcPCO2.Conclusions: No significant differences were observed in cerebral hemodynamics when the nCPAP pressure was set to 4-8 cmH2O.